A Psycholinguistic Analysis of the Students’ Perceptions Used Google Classroom as Online Learning Media During Pandemic - Ithriyah, Siti; Roslaini (HM Publisher, 2023)
Since COVID-19 case is increasing rapidly, many students and teachers must do the teaching and learning process online. Google Classroom has been the most used online learning media chosen by teachers and students during the pandemic. This study aimed to explore how psycholinguistic factors and students' perceptions of the Google Classroom application impacted their remote learning experiences amidst the COVID-19 pandemic. This research applied mixed-method in order to answer the research questions. For collecting the data, the researcher utilized the close-ended questionnaire carrying 6 indicators about the student's perceptions of Google Classroom, which were then analyzed quantitatively and used the interview analyzed qualitatively. The questionnaires were given to 33 students as participants. Google Classroom did help the students receive the course materials well and make students become more productive, disciplined, responsible and independent throughout the learning process during the pandemic. The highest percentages of ease of learning Google Classroom (84.85%), and ease of accessing Google Classroom (83.35%), whilst perceived usefulness of Google Classroom (76.08%) and students’ satisfaction with Google Classroom (74.28%) were in the good category.